(40-u-5(12-u))=0

Simple and best practice solution for (40-u-5(12-u))=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (40-u-5(12-u))=0 equation:


Simplifying
(40 + -1u + -5(12 + -1u)) = 0
(40 + -1u + (12 * -5 + -1u * -5)) = 0
(40 + -1u + (-60 + 5u)) = 0

Reorder the terms:
(40 + -60 + -1u + 5u) = 0

Combine like terms: 40 + -60 = -20
(-20 + -1u + 5u) = 0

Combine like terms: -1u + 5u = 4u
(-20 + 4u) = 0

Remove parenthesis around (-20 + 4u)
-20 + 4u = 0

Solving
-20 + 4u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 4u = 0 + 20

Combine like terms: -20 + 20 = 0
0 + 4u = 0 + 20
4u = 0 + 20

Combine like terms: 0 + 20 = 20
4u = 20

Divide each side by '4'.
u = 5

Simplifying
u = 5

See similar equations:

| 14+1.4x=8.4 | | 6(4-6x)+5(3-5+2x)=0 | | 4a+44=7a-4 | | 3+78=52x+19 | | 6r^2-2r-3=0 | | 6x^3-10=0 | | 4x-8=88-8x | | 9x(x)=7-5x | | 5x-1=2(3x+2) | | 96-4x=148 | | 7x+5=3x-27 | | t(n)=-5n+2 | | 3d+4=39 | | 4.9(4.9x-4)=-4x+5.3 | | -38=2(4x-3) | | 3(x+4)+8=-7 | | 10x-3.2=-6x+7.2 | | 15=-4(5k-2)+4(1+5k) | | 7x-(2x-18)=58 | | 20-6x=-75-9x | | 4(x-1)-10=-38 | | 3m-2p-4m-p= | | -8c+4v-5= | | W+15-28+5=117 | | 13=7+3u | | 5x+7=-38-6x | | 3log(x)-4log(x+3)+log(y)= | | 9x*2-25y*2=-1 | | 1+4x=1+x | | 5y^2=35 | | -0.8w=5 | | p-24=4(5p-6) |

Equations solver categories